(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This paper uncovers the significance of ecommerce in Indian economy. As we as a whole realize India is among the quickest developing economy of the world , in this manner it is especially critical to have government mediation and tremendous venture inflow in type of Foreign direct interest in substantial economy like India to balance out and increment the development of ecommerce industry in the economy. In India with the digital economy entrance has expanded essentially, as per measurable information web use has expanded to 429.23 million client in India and is relied upon to stretch around 830m by year 2021 .There has been huge ascent of web based business in India, as India’s web economy is 125 billion dollar in 2017. In this paper we will look towards the job of government in ecommerce industry and furthermore look towards the different obstructions of web based business in Indian aspects.In this exploration paper we will speak basically about B2C Ecommerce and its level of total national output in Indian economy.